Author Correction: Potential damaging mutation in LRP5 from genome sequencing of the first reported chimpanzee with the Chiari malformation - Manuel Solis-Moruno (Nature Portfolio, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.